Further characterization of an adenosine-containing modification of vaccinia virus proteins - Child, Stephanie J.; Hruby, Dennis E. (Biochimica et biophysica acta, 1993)
Three vaccinia virus (VV) core proteins which become labeled when virus is grown in the presence of radiolabeled adenosine or orthophosphate were identified as the major viral core proteins 4A, 4B, and 25K on the basis of comigration with [[ 35 S]methione-labeled viral proteins and immunoprecipitation with monospecific polyclonal antisera. Boronate affinity chromatography and HPLC analysis suggested that a cis-diol-containing adenosine compound is present on this set of viral proteins. The replication of VV in tissue culture cells was prevented by the ADP-ribosylation inhibitors nicotinamide (NIC), 3-aminobenzamide (3-AB), and meta-iodobenzylguanidine (MIBG). None of these compounds significantly affected viral DNA synthesis at lower drug concentrations, although at higher concentrations of the three drugs a reduction in viral DNA synthesis was evident. Total VV protein synthesis also decreased at higher inhibitor levels, and the proteolytic processing of the major virion core proteins was greatly diminished as well. The three inhibitors also affected labeling of viral core proteins and cellular histone proteins by [8- 14C]adenosine. In addition, mature, infectious virus particles were not formed in the presence of either 60 mM NIC or 3-AB, or 0.6 mM MIBG. These results provide evidence that the major VV core proteins are subject to modification by an adenosine compound, and suggest the possibility that this modification might represent ADP-ribosylation.